A Standardised Method to Quantify the Infectious Titre of Rabbit Haemorrhagic Disease Virus - Tiffany W. O’Connor; Damian Collins; Andrew J. Read; Paul M. Hick; Peter D. Kirkland (Viruses)
Quantifying the infectious titre of preparations containing rabbit haemorrhagic disease virus (RHDV) is an essential virological technique during RHDV research. The infectious titre of an RHDV preparation is determined using a bioassay to identify the endpoint dilution at which 50% of rabbits become infected (RID50). Previous publications have briefly described the method for estimating the infectious titre of RHDV preparations by challenging rabbits with 10-fold serial dilutions. However, these descriptions lack the critical considerations for a standardised method to estimate RID50. These details are presented here, along with a comparison between the Reed–Muench, Dragstedt–Behrens, Spearman–Kärber, and probit regression methods for calculating the RID50. All the statistical approaches demonstrated a high level of agreement in calculating the RID50. To help assess the precision of the estimated infectious titre, the improved Spearman–Kärber and probit regression methods provide the 95% confidence intervals. The method outlined improves the accuracy of results when undertaking studies of pathogenicity, host resistance, and the production of vaccines against RHDV.